The effects of psychotherapy for depressed or posttraumatic stress disorder women with childhood sexual abuse history: Meta-analysis of randomized controlled trials. Issue 17 (April 2020) - Lu, Jhih-Yuan; Tung, Tao-Hsin; Shen, Sheng-Ang; Huang, Chien; Chen, Pei-Shih
Abstract: Background: Depression and posttraumatic stress disorder (PTSD) are the most common mental disorders of women suffered from childhood sexual abuse histories. It has been widely recognized that depression and PTSD may decrease patients' quality of life. The objective of this study is conducted to explore the effects of psychotherapy for depressed or PTSD women with childhood sexual abuse history. Methods: We searched the PubMed and Cochrane Library from inception to June 30, 2019. The search strategy is (sexual assault OR sexual crime OR sexual abuse) AND (depression OR PTSD) AND (treatment OR intervention OR psychotherapy) with no restriction on language. Two authors independently selected the studies, assessed the quality of the included studies, and extracted data. Results: Nine randomized control trials with 761 participants met the inclusion criteria. There were 340 participants in the psychotherapy group and 421 participants in the control group (usual treatment or waiting list). Compared to usual care, improvements were significantly greater in the psychotherapy group. The Beck depression inventory score for depression diagnosis of the psychotherapy group is lower from 4.27 to 8.96 ( P  < .05) than the control group. The client assessment protocols for PTSD, the diagnosis is also lower from 12.4 to 13.71 than the control group ( P  < .05). Conclusion: The results suggested that psychotherapy is effective in reducing depressed or PTSD women with childhood sexual abuse. Further large-scale high-quality randomized controlled trials with long-term follow-up are warranted for confirming this finding.